2021
DOI: 10.1007/s10029-021-02372-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of inguinal hernia repair: the influence of clinical and hernia-specific factors

Abstract: Introduction As in the rest of the world, in Germany, inguinal hernia operations are among the most common operations. From an economic standpoint, very little is known about the influence of demographic, clinical or hernia-related parameters on the cost of inguinal hernia repair. We, therefore, evaluated individual patient parameters associated with higher costs with a special focus on multimorbidity. Methods A total of 916 patients underwent hernia repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 19 publications
1
13
1
12
Order By: Relevance
“…Males are 25 times more likely to have inguinal hernia than females; this observation is consistent with our findings. The mean age of patients in our study was 36 ± 11 years, which contradicts the previous studies that showed that the mean patient age was above 49 years [10,11]. To the best of our knowledge, this may allude to the patient's health education level and early engagement with the healthcare system.…”
Section: Discussioncontrasting
confidence: 99%
“…Males are 25 times more likely to have inguinal hernia than females; this observation is consistent with our findings. The mean age of patients in our study was 36 ± 11 years, which contradicts the previous studies that showed that the mean patient age was above 49 years [10,11]. To the best of our knowledge, this may allude to the patient's health education level and early engagement with the healthcare system.…”
Section: Discussioncontrasting
confidence: 99%
“…We reported a higher operative time (17 ± 47.2 minutes) and length of hospitalization (2.42 ± 3.48 days) than has been reported in the literature [10,12,17,18]. Our hospital admission policy and the fact that it is an educational institution can explain this difference.…”
Section: Discussionmentioning
confidence: 40%
“…In addition to the technical difficulties and a long learning curve, in Italy, a further obstacle to the spread of the laparoscopic technique has been the remuneration of the operation that, regardless of whether the hernia was monolateral, bilateral or recurrent, is remunerated in the same way as a monolateral open hernioplasty. Although some recent studies have reported advantages in healthcare expenditure for laparoendoscopic procedures, this figure is probably distorted by the type of healthcare system adopted in each country [ 16 , 17 ]. In some countries, the healthcare systems are welfarist, while in others, they are purely insurance-based, and in others still, they are mixed, so the impact of the reimbursement system could affect the push for health insurance in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper by Aydin et al showed that the cost of an anterior approach is similar to TAPP. However, the costs of hospital stay and anesthesia for each type of procedure are not reported, and bilateral and recurrence are compared [ 17 ]. The preperitoneal and transperitoneal approach does not seem to be related to a difference in expenditure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation